Study on Chloroquine Resistance Transporter (pfcrt) Gene Polymorphism of Plasmodium falciparum in Malaria Patients in Lampung - Marlina Kamelia; Supargiyono -; Mahardika Agus Wijayanti (Pusat Kedokteran Tropis, 2011)
Introduction: The prevalence of malaria in Lampung Province was increased in the last few years. One of the factors contributes to the increased rate is the widespread of the Plasmodium falciparum resistance to antimalarial drugs. Mutation on the gene encoding Pfcrt protein has been reported to be correlated with this resistance.Objectives: To fi nd out the frequency and distribution of the pfcrt gene polymorphism among Plasmodium falciparum in malaria patients in endemic area at Bandar Lampung and Lampung Selatan, LampungProvince.Methods: Blood samples were collected from malaria falciparum patients in Bandar Lampung and Lampung Selatan by active and passive case detections. Two to three mL of venous blood were collected in tubes with EDTA, and kept in the temperature of -200C before DNA extraction. DNA from each sample was extracted using Guanidine isothiocyanate and Chelex 100 methods. Genes encoding Pfcrt protein were amplifi ed by Nested PCR using TCRP and TCRD primers. The polymorphism of the pfcrt gene was identified by cutting the PCR product using Apo1 restriction enzymes to produce 100bp and 34bp fragments.Results: Forty six samples from P. falciparum-infected patients were collected from the two areas. The genes encoding the Pfcrt protein were succesfully amplifi ed, all 46 PCR products showed 100bp and 34bpfragments after incubation with Apo1 restriction enzyme. It indicated that pfcrt polymorphism was 100%.Conclusion: The frequency of pfcrt gene polymorphisms in patients with malaria falciparum in Bandar Lampung and Lampung Selatan was 100%.Keywords: malaria falciparum, pfcrt, chloroquine, polymorphism